Perioperative Identification and Management of Hyperglycemia in Orthopaedic Surgery. (7th December 2022) - Lamanna, Daniel L.; McDonnell, Marie E.; Chen, Antonia F.; Gallagher, John M.
Abstract : ➤ The consequences of undermanaged perioperative hyperglycemia are notable and can have a serious impact on adverse postoperative outcomes, especially surgical site infections and periprosthetic joint infections (PJIs). ➤ Preoperative screening of hemoglobin A1c with a goal threshold of <7.45% is ideal. ➤ There are a variety of risk factors that contribute to hyperglycemia that should be considered in the perioperative period, including glucocorticoid use, nutritional factors, patient-specific factors, anesthesia, and surgery. ➤ There are expected trends in the rise, peak, and fall of postoperative blood glucose levels, and identifying and treating hyperglycemia as swiftly as possible are the fundamental aims of treatment and improved glucose control. Performing frequent postoperative blood glucose monitoring (in the post-anesthesia care unit, on the day of surgery at 1700 and 2100 hours, and in the morning of postoperative day 1) should be considered to allow for the early detection of alterations in glucose metabolism. In addition, instituting a postoperative dietary restriction of carbohydrates should be considered. ➤ The use of insulin as a hypoglycemic agent in orthopaedic patients is relatively safe and is an effective means of controlling fluctuating blood glucose levels. Insulin therapy should be administered to treat hyperglycemia at ≥140 mg/dL when fasting and ≥180 mg/dL postprandially. Insulin therapy should be ceased at blood glucose levels of <110 mg/dL; however, monitoring for glycemic dysregulation should be continued. In all cases of complex diabetes, consultation with diabetes specialty services should be considered. ➤ The emerging use of technology, including continuous subcutaneous insulin pump therapy and continuous glucose monitoring, is an exciting area of further research and development as such technology can more immediately detect and correct aberrations in blood glucose levels.